Decolonisation and regional geopolitics - Passemiers, Lazlo, author.
1 online resource.
Keywords: Decolonisation and Regional Geopolitics argues that as much as the 'Congo crisis' (1960-1965) was a Cold War battleground, so too was it a battleground for Southern Africa's decolonisation. This book provides a transnational history of African decolonisation, apartheid diplomacy, and Southern African nationalist movements. It answers three central questions. First, what was the nature of South African involvement in the Congo crisis? Second, what was the rationale for this involvement? Third, how did South Africans perceive the crisis? Innovatively, the book shifts the focus on the Congo crisis away from Cold War intervention and centres it around African decolonisation and regional geopolitics.